PENGARUH CAPITAL ADEQUACY RATIO, RETURN ON ASSET, LOAN TO DEPOSIT RATIO, NON PERFORMING LOAN, DAN NET PROFIT MARGIN TERHADAP PERUBAHAN LABA (Perusahaan Perbankan yang Terdaftar di BEI periode 2007 â 2010) - SE, M.Si, Ak, Murtini; Gayatri, Serli (STIE Muhammadiyah Pekalonga, 2011)
This research has a purpose to provide empiris about factors that affect to earning changes. The examined factors in this research are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return On Asset (ROA), Non Performing Loan (NPL), and Net Profit Margin (NPM).Methodology this research as the sample used proposive sampling with criteria as (1) banking companies which listed at JSX who provide financial report year ending 31st December during the observation period 2007 â 2010, well available at ICMD and annual report. (2) Companies must be listed at beginning period of the observation and not delisting until the end of observation. (3) during the period of observation, banking companies does not a merger and acuisition. (4) the banking companies have a positive earning during period of the observation. technic analysis with multi linier regression and hypothesis test used partial t-test and simultan F-test at level of significance 5 percent and adjusted R square.From the result of analyze show that as a partial CAR, LDR, ROA, and NPL have an influence to earning changes of banking companies which listed in JSX during period 2007 â 2010 at level of significance less than 5 percent. And F-test show that five independent variable CAR, LDR, ROA, NPL, and NPM have a influence to earning changes at level of significance less than 5 percent. Predictable of the five variables to earning changes is 27 percent which indicated by the value or adjusted R square 27 percent, and left over it 73 percent is affected by other factors are not included in this research.Key words : Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return On Asset (ROA), Non Performing Loan (NPL), Net Profit Margin (NPM), and Earning Changes.